A preliminary examination of teachers’ and parents’ perspective on sexually inclusive primary education: The role of homophobic prejudice and moral disengagement - Touloupis, Thanos; Pnevmatikos, Dimitrios (Frontiers in Education, 2024)
Sexually inclusive primary education, namely a school environment that uses inclusive practices towards sexual minorities contributes to students' psychological and learning adaptation. Therefore, it is essential primary school stakeholders' perspective on sexually inclusive education to be explored, since this could facilitate the effective implementation of related prevention/awareness programs targeted at students. Nevertheless, teachers' and parents' related perspectives, as main school stakeholders, as well as the predictive value of their homophobic prejudice and moral disengagement remain an under-investigated research field. The present study examined comparatively teachers' and parents' perspectives on sexually inclusive primary education. Furthermore, the predictive role of homophobic prejudice and moral disengagement was investigated for each subgroup. Overall, 249 primary school teachers (78% women) of the fifth and sixth grades from randomly selected Greek public schools and 268 parents (81% mothers) of children who attended the above grades of the participating schools completed an online self-reported questionnaire on the variables involved. In general, participants expressed a relatively conservative perspective on sexually inclusive primary education, with teachers' perspective being less inclusive than that of the parents. Teachers' related perspective was predicted negatively mainly by homophobic prejudice and secondarily by moral disengagement. Parents' corresponding perspective was predicted negatively only by moral disengagement. Despite the differentiated perspective between the two subgroups, the findings imply that both teachers and parents need to attend prevention/awareness actions regarding students' sexual diversity and their school inclusion. Within these actions, differentiated experiential activities could be implemented for teachers and parents to combat homophobic prejudice and/or moral disengagement.